Thermal insulation material produced from recycled materials for building applications: cellulose and rice husk-based material - Marín-Calvo, Nacarí; González-Serrud, Sergio; James-Rivas, Arthur (Frontiers in Built Environment, 2023)
Construction materials derived from agro-industrial waste are increasingly attractive in the building sector, due to their sustainability and lower environmental impact. Hence, in recent years worldwide the amount of research and publications tending to the development of materials that take advantage of residues from agro-industrial activities has increased. The role of thermal insultation materials in the building envelope is significant, especially in hot-humid region.This study presents the manufacturing and evaluation of a cellulose and rice husk-based insulation material, as a proposal for the reuse of materials considered as value-added waste, such as recycled paper and rice husks. Boards and test specimens were elaborated, as well as mechanical and thermal tests. The material was evaluated by means of thermal tests, in accordance with ASTM C177, to measure the thermal conductivity. Tensile and compressive strength tests were performed, based on ASTM C209 and ASTM C39 Standard, respectively. According to the results obtained, the material shows a thermal coefficient of 0.04 W/m•K which corresponds to a material with the potential to thermally insulate an enclosure. Maximum stresses were obtained for the 3 compositions in average for a range between 1.31 and 1.76 MPa. Ultimate compressive strength obtained was between 20.19 and 21.23 MPa. The proposed material is presented as a sustainable alternative, which can be used in the field of environmentally friendly buildings, which contribute to reducing the carbon footprint, by energy savings.This is a provisional file, not the final typeset article are mostly manufactured from petrochemical sources (Carlos Javier et al., 2023). Production and manufacturing processes of construction materials account a higher carbon footprint, polluting air, land, and water (Maraveas, 2020). Construction materials derived from agro-industrial waste are increasingly attractive in the construction sector, due to their sustainability and lower environmental impact. Hence, in recent years the amount of research and publications tending to the development of materials that take advantage of residues from agro-industrial activities has increased (Chabannes et al.